A survey of DNA methylation across social insect species, life stages, and castes reveals abundant and caste-associated methylation in a primitively social wasp - Weiner, Susan A.; Galbraith, David A.; Adams, Dean C.; Valenzuela, Nicole; Noll, Fernando B. [UNESP]; Grozinger, Christina M.; Toth, Amy L. (Springer Nature, 2013)
DNA methylation plays an important role in the epigenetic control of developmental and behavioral plasticity, with connections to the generation of striking phenotypic differences between castes (larger, reproductive queens and smaller, non-reproductive workers) in honeybees and ants. Here, we provide the first comparative investigation of caste- and life stage-associated DNA methylation in several species of bees and vespid wasps displaying different levels of social organization. Our results reveal moderate levels of DNA methylation in most bees and wasps, with no clear relationship to the level of sociality. Strikingly, primitively social Polistes dominula paper wasps show unusually high overall DNA methylation and caste-related differences in site-specific methylation. These results suggest DNA methylation may play a role in the regulation of behavioral and physiological differences in primitively social species with more flexible caste differences. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: DNA methylation; Epigenetics; Eusociality; Hymenoptera; Phenotypic plasticity; Vespidae; ant; caste; DNA; entomology; eusociality; honeybee; methylation; phenotypic plasticity; physiology; social insect; wasp; Apis mellifera; Apocrita; Apoidea; Formicidae; Hexapoda; Polistes; Polistinae